Emotions and Sense of Self-Efficacy of Pre-Service English Teachers - María del Rosario Reyes-Cruz (Universidad Autónoma de Baja California, 2020)
The aim of this study was to explore changes in the emotional states and sense of self-efficacy of trainee English teachers in their teaching internship, establish the relationship between these two constructs, and determine the trigger of these emotional states. A qualitative exploratory design was employed to conduct the study, which involved ten pre-service English teachers. The findings indicate that all student teachers experienced negative emotional states at the beginning of their internship, which were triggered by the fact they were giving classes. Their sense of self-efficacy was initially low, but gradually increased over the course of their intership. Their emotions also shifted from negative to positive over the same period. Negative emotions appear to produce a low sense of self-efficacy in the way positive ones lead to a high sense of self-efficacy.